Recent advances in the use of biogenic nanomaterials and photocatalysts for wastewater treatment: challenges and future prospects - Sanni, Samuel Eshorame; Oni, Babalola Aisosa; Okoro, Emeka Emmanuel; Pandya, Shivani (Frontiers in Nanotechnology, 2024)
In many parts of the world, the availability of clean water is almost an impossible task owing to the intrusion of contaminants in flowing or stagnant streams which renders them unsafe for use by man. Water pollution is a serious environmental problem that poses serious dangers to humans, the environment and aquatic life. Also, the recent rise in the spate of emerging contaminants as well as bacteria in waters recovered from process streams, manufacturing and other production activities, have resulted in unforeseen consequences including environmental pollution, health related sicknesses (diarrhoea, dysentery, cholera, skin irritations, lung infection etc.) as well as loss and extinction of aquatic lives, hence, the need to consider viable methods of treating waste waters so as to render them safe for use by these organisms. This will in turn preserve life below water-SDG 14 as well as promote the use of clean water and a healthy environment-SDG 6. Among the several existing nanotechnologies tailored towards the treatment of wastewater, a couple of inorganic toxic nanomaterials/nanosubstances have been adopted which render such treated waters as potential risks to humans and aquatic lives. However, green nanoparticles are considered potent and viable means of treating these waters, especially when literature has it that some nanomaterials are toxic in nature. Furthermore, the paper also reports on some unpopular but very potent emerging green nanomaterials, alongside recent advances, applications, related challenges and ways to address them. Information on future prospects of green nanoparticles as potential long-term sustainable water purification and wastewater treatment technologies are also included; therefore, this study is focused on addressing issues related to SDGs 3 (ensure healthy lives and promote well-being), 6 (clean water and sanitation), 12 (responsible consumption and production) and 14 (life below water).